PENERAPAN KONSEP CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA SISTEM INFORMASI PENYEWAAN LAPANGAN FUTSAL DI SWADAYA FUTSAL PALEMBANG - Hardini Novianti; Allsela Meiriza; Nurul Izmy (Universitas Sriwijaya, 2016)
AbstractSwadaya Futsal Palembang is a rental futsal court services company. Therefore, in order Swadaya Futsal Palembang to continue compete then applied the concept of Customer Relationship Management information systems leasing futsal field to establish a relationship with the customer. System development methods in this study using the FAST (Framework for the Application of Systems Techniques), while the programming language used PHP and MySQL as the database. The result of applying of Customer Relationship Management information systems rental futsal field makes the presentation of information and service can be more quickly and easily.Keywords : Customer Relationship Management (CRM), FAST (Framework for the Application of Systems Techniques), Futsal, Website.AbstrakSwadaya Futsal Palembang adalah perusahaan yang bergerak di bidang jasa penyewaan lapangan futsal. Agar Swadaya Futsal Palembang dapat terus bersaing maka diterapkan konsep Customer Relationship Management dalam sistem informasi penyewaan lapangan futsal untuk menjalin hubungan dengan pelanggan. Metode pengembangan sistem dalam penelitian ini menggunakan FAST (Framework for the Application of Systems Techniques), sedangkan bahasa pemograman yang digunakan PHP dan MySQL sebagai basis data. Hasil dari penerapan konsep Customer Relationship Management dalam sistem informasi penyewaan lapangan futsal ini menjadikan penyajian informasi dan pelayanan dapat lebih cepat dan mudah.Kata kunci : Customer Relationship Management (CRM), FAST (Framework for the Application of Systems Techniques), Futsal, Website.